Reducing the aerodynamic drag of commercial vehicles. (5th August 2014) - Garry, K.P.; Stollery, J.L.
Rising fuel costs in recent years have increased the importance of vehicle aerodynamic drag; even modest reductions can now show significant benefits in truck operating costs. Such potential benefits have prompted an extensive research programme aimed at reducing the drag of existing vehicles and defining the changes of shape needed for the next generation of fuel efficient vehicles. The results of wind tunnel tests on a variety of scale models are presented in order to identify both the problems of existing designs and the opportunities for improvement. The significant areas of interest are the cab/container geometry and the design of the container forebody, and studies are included concerned with methods of significantly varying the drag, usually by incorporating 'add–on' devices. The problems of cross–wind drag characteristics are covered, together with measurements on the effectiveness of gap flow control and underbody modifications to improve the characteristics of the vehicle in yaw.